2005
DOI: 10.1021/jp051797p
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Orientation of Tetraalanine in a Lyotropic Liquid Crystal Studied by Nuclear Magnetic Resonance

Abstract: The (1)H NMR spectra of two isotopomers of tetraalanine deuterated on the two external methyl groups and on the two internal ones, respectively, were recorded in the lyotropic solvent cesium pentadecafluorooctanoate (CsPFO)/water. Eight dipolar couplings could be estimated from the spectra. The set of dipolar couplings was fitted assuming that one rigid conformer is present. Of the four major conformers considered, selected on the basis of theoretical calculations, the one characterized by the two couples of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 45 publications
7
13
2
Order By: Relevance
“…In particular, the combination of Polarized Raman, Fourier transform-IR and vibrational circular dichroism indicated that the dihedral angles of the two internal residues of cationic tetraalanine are close to the Ramachandran coordinates of the polyproline II helix (PPII). Further evidence supporting these results was given by us in a previous paper [11], where we presented a liquid-crystal 1 H NMR study on the conformation and orientation of tetraalanine in the lyotropic solvent cesium pentadecafluorooctanoate=water (CsPFO=D 2 O). This system is known to form bilayer-like disk-shaped micelles with average alignment of the disks perpendicular to an external magnetic field [12], which induces alignment also on solute molecules.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…In particular, the combination of Polarized Raman, Fourier transform-IR and vibrational circular dichroism indicated that the dihedral angles of the two internal residues of cationic tetraalanine are close to the Ramachandran coordinates of the polyproline II helix (PPII). Further evidence supporting these results was given by us in a previous paper [11], where we presented a liquid-crystal 1 H NMR study on the conformation and orientation of tetraalanine in the lyotropic solvent cesium pentadecafluorooctanoate=water (CsPFO=D 2 O). This system is known to form bilayer-like disk-shaped micelles with average alignment of the disks perpendicular to an external magnetic field [12], which induces alignment also on solute molecules.…”
Section: Introductionsupporting
confidence: 79%
“…The doublets due to methyl protons resonate at 1.66, 1.53, and 1.46 ppm, the intensity of the signal centered at 1.53 ppm being double than each of the others. On the basis of previous assignment [11], these signals were attributed to the methyl groups of the N-terminal alanyl residue, of the two inner residues, and of the C-terminal residue, respectively. Because the H N protons readily exchange with D 2 O, they are not observed in the 1 H spectrum.…”
Section: Results and Discussion 1 H Nmr Of A 4 In The Isotropic Phasementioning
confidence: 84%
See 3 more Smart Citations